LA VILLA RENACENTISTA (I) - Sánchez-Rojas Fenoll, María del Carmen (Imafronte, 1986)
This paper constitutes the First part of a study on the villa of the Renaissance in general, and more in particular on the Palladian villa. Historical antecedents already existing in Egypt, Babylon and Persia are commented upon. with special reference to the Roman villa, because of the importance it was to have in the implementation of the later typology of the villas. Subsequently the different types established by Vitrubio, Ackermann, Francesco Doni and Frommel are examined, as well as the role of authors such as Alberti or Francesco di Giorgio, who wrote on this subject. Futher on, the article comprises a socio-econornic study on the circumstances artending the development of villas in the XVIth century, Finally grouping in three sections the basic conditions that form the typology of the villas. These groups are the following: 1st: The group constituted by historical conditions. 2nd: The group constitured by cultural conditions. 3nd: The group constituted by socioeconomic conditions.